The Effect of Motor Pathway Control As A Style For Learning Some Basic Skills In Floor Exercises In Men's Gymnastics - Ahmed, Nazm (Journal of Physical Education, 2017)
The aim of the research is using motor pathway control as a teaching stylethrough using exercise according to performance indicators. The researcher used theexperimental method. The subjects were (40) sophomore students of physical education andsport Sciences College. The exercises were designed according to proposed style for theskills. The data was collected and treated using proper statistical operations. The researcherconcluded that controlling motor pathway affects using motor abilities and concentration oncompound muscular groups as well as controlling the motor pathway achieves better positionfor body center during practice. Finally the researcher recommended using motor pathwaycontrol on freshmen and during the first stages of learning and training as well as using it fordeveloping special muscular groups and to reduce the variables affecting using mentalabilities.